Synthesis of Ketenaminals via Catalyst-Free Hydroamination of Ynamides and Diphenylsulfonimide - Yu, Lian; Deng, Yuan; Cao, Jian (Synthesis, 2015)
A novel regio- and stereoselective synthesis of ketenaminals by catalyst-free hydroamination of ynamides with diphenylsulfonimide under mild conditions is reported. In addition, N-sulfonylamidines are prepared via subsequent desulfonylation reaction.
Keywords: amides; amination; imides; alkynes; sulfonamides; desulfonylation